1999
DOI: 10.1080/002077299292038
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear time series modelling with the radial basis function-based state-dependent autoregressive model

Abstract: This paper investigates nonlinear time series modelling using the general state-dependent autoregressive model. To achieve the estimate of the model, an attempt is made to approximate the state-dependent parameter by employing the Gaussian radial basis function for its universal approximation capability. As a result, a radial basis function-based autoregressive (RBF-AR) model is derived which has a form similar to a generalized exponential autoregressive model. To reach the applicability of the RBF-AR model, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 12 publications
2
39
0
Order By: Relevance
“…Particularly, the radial basis function neural network (RBFNN) is known for its strengths of simple topological structure and fast learning [18,28]. Both theoretical and experimental analysis [31,34] indicated that the RBFNN could approximate any functions and identify nonlinear systems by using members of a family of basis functions. The RBFNN is a three-layer feed-forward network that generally uses a linear transfer function for the output units and a nonlinear transfer function (typically the Gaussian function) for the hidden units.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the radial basis function neural network (RBFNN) is known for its strengths of simple topological structure and fast learning [18,28]. Both theoretical and experimental analysis [31,34] indicated that the RBFNN could approximate any functions and identify nonlinear systems by using members of a family of basis functions. The RBFNN is a three-layer feed-forward network that generally uses a linear transfer function for the output units and a nonlinear transfer function (typically the Gaussian function) for the hidden units.…”
Section: Introductionmentioning
confidence: 99%
“…The idea behind this definition is that the term exp Àk k max tÀ1 kXðt À 1Þ À Z 0 k k 2 2 n o should approach zero when the state X(t À 1) is far away from the center Z k , so that the linear weights are bounded and stable [29,25]. After selecting an initial nonlinear parameter vector h 0 N , and keeping it fixed, use the LSM to compute the initial linear weights h 0 L :…”
Section: Initializationmentioning
confidence: 99%
“…For the model order selection, several methods have been proposed, e.g., the Akaike Information Criterion (AIC) [1] and cross validation [18,20,22]. Shi et al [29] and Peng et al [25] suggest the use of the AIC as the RBF-AR model selection criteria. Although the AIC may not be the best model selection method when the data comes from a mathematical model [28], it may give a good synthetic result for modeling the data where an exact mathematical model for the data does not exist.…”
Section: Estimation Of the Llrbf-ar Modelmentioning
confidence: 99%
See 2 more Smart Citations